Transforming Learners’ Engagement: Reflections on a Continuing Medical Education Program - Richard A. Prayson; Catherine H. Monaghan (Adult Education Research Conference, 2014)
Continuing education at most medical meetings rely heavily on didactic methodologies. Attendees expect this approach in a Continuing Medical Education (CME) program and are surprised when another approach is taken. This roundtable paper briefly examines how adult educators can begin changing the culture of CME for physicians.